Pathophysiology of Ketamine Neurotoxicity: An Overview - Aydin, Mustafa; Deveci, Ugur (Elsevier Inc., 2016)
Ketamine, an N-methyl-. d-aspartate (NMDA) receptor antagonist, is widely used for general anesthesia in pediatric practice. Significant safety concerns regarding the use of anesthesia during early development have arisen since the animal studies indicating administration of an NMDA receptor antagonist during the early stages of central nervous system development can produce neurotoxicity. A growing number of evidences in rodents and nonhuman primates have indicated that exposure to repeat doses of ketamine can induce neuroapoptosis and damage in the developing brain, mainly hippocampal neurodegeneration, causing persistent learning and memory impairment. However, the precise mechanisms of ketamine neurotoxicity are not completely understood. It is indicated that the upregulation of the NMDA type of glutamate receptors is responsible from ketamine-induced neurotoxicity by causing to a toxic accumulation of intracellular calcium. Neuronal apoptosis via reactive oxygen species-mediated mitochondrial pathway plays pivotal role in the ketamine neurotoxicity. Ketamine also alters the cortical neurogenesis of neural stem progenitor cells through a different manner. Thus, there is a growing need to develop innovative strategies to prevent this injury. © 2016 Elsevier Inc. All rights reserved.
Keywords: Apoptosis; Brain; Calcium; Development; General anesthesia; Glutamate; Ketamine; Mitochondria; N-methyl-d-aspartate receptor; Neurotoxicity; Reactive oxygen species